Energy Management of Fast Charging and Ultra-Fast Charging Stations With Distributed Energy Resources - Sony Susan Varghese; Syed Qaseem Ali; Geza Joos (IEEE Access, 2024)
Dependence on the depleting fossil fuels, particularly in the transportation sector, calls for sustainable, green solutions such as electrification, which address the challenges of providing alternate sources of power at low emissions. Electric vehicles are the centerpiece of the transportation electrification sector. Reducing the time for charging from hours to a few minutes gives an extra sheen to the prospect of transportation electrification. However, massive upscaling of the electric power infrastructure is required to accommodate the demands of large-scale transportation electrification. This article explores a sustainable strategy involving distributed energy resources to meet the elevated power and energy demand due to DC fast charging and ultra-fast charging EV load on the electric power distribution network. The mixed integer quadratic optimization model developed ensures seamless integration of the renewable resources, the EV load, and the distribution grid while adhering to the power quality constraints. This paper demonstrates that it is possible to serve a 155 kW aggregated (peak power load) DC fast charging load with a 100 kW interconnect. Similarly for an ultrafast -charging station a peak reduction factor of 9.11 compared to unmanaged charging is achieved at the interconnection point. The methodology is developed, and results are compared against a rule-based system for multiple scenarios. Additionally, validation based on OPAL RT RT-4500 for a sample scenario is presented.